LEADERSHIP AND MANAGEMENT AND ITS ROLE IN STRATEGIC CHANGE - JOKIĆ, Svetlana; ILIC, Milena; RANKOVIĆ, Marko; MITIĆ, Branislav (Annals of Spiru Haret University. Economic Series, 2019)
Leadership and management, as two important processes in organizations, have a significant impact on all interactions and other processes that occur within an organization. The process of strategic change, important for the survival of organizations in turbulent times, is also conditioned by the roles of managers and leaders and their coordination of resources, vision, and the like. The aim of the paper is to demonstrate the influence of managers and leaders on strategic change (strategy implementation), through secondary and primary research.